Performance of Operational Inflow Forecasting System for Hydropower Reservoir - Basri H.; Mohd Sidek L.; Abdul Razad A.Z.; Mohd Salleh S.R.; Kamarulzaman M.S.; Pokhrel P. (Springer, 2023)
The inflow forecasting system is an essential tool to assist dam owners in decision making and planning. Effective and optimized hydropower reservoir operation, monitor and forecast inflows and lake level to provide benefits in maximizing energy revenue, while taking into account dam safety risks. The Temengor Inflow Forecasting System for Temengor dam was developed in a robust system that runs on a real-time modeling platform. Reservoir inflow forecast results must be able to provide a timely and accurate forecast for appropriate reservoir management. Thus, it is essential to monitor the performance of the forecasting system to ensure the developed system is performing to its maximum potential. This paper discussed the performance of the Temengor inflow forecasting system. In general, the comparison of forecast model results with observed data shows that the model is able to provide good forecast accuracy. Continuous model performance monitoring enables reliable forecast results, which can be used for future resource availability for hydropower generation and advance warning of water-related disasters such as a flood. 2020, Springer Nature Singapore Pte Ltd.